MEASUREMENT OF ILLITE PARTICLE THICKNESS USING A DIRECT FOURIER TRANSFORM OF SMALL-ANGLE X-RAY SCATTERING DATA - Shang C.; Rice J.A.; Eberl D.D.; Lin J.-S. (My University, 2003)
It has been suggested that interstratified illite-smectite (I-S) minerals are composed of aggregates of fundamental particles. Many attempts have been made to measure the thickness of such fundamental particles, but each of the methods used suffers from its own limitations and uncertainties. Small-angle X-ray scattering (SAXS) can be used to measure the thickness of particles that scatter X-rays coherently. We used SAXS to study suspensions of Na-rectorite and other illites with varying proportions of smectite. The scattering intensity (I) was recorded as a function of the scattering vector, q = (4 pi/lambda) sin(theta/2), where lambda is the X-ray wavelength and theta is the scattering angle. The experimental data were treated with a direct Fourier transform to obtain the pair distance distribution function (PDDF) that was then used to determine the thickness of illite particles. The Guinier and Porod extrapolations were used to obtain the scattering intensity beyond the experimental q, and the effects of such extrapolations on the PDDF were examined. The thickness of independent rectorite particles (used as a reference mineral) is 18.3 Angstrom The SAXS results are compared with those obtained by X-ray diffraction peak broadening methods. It was found that the power-law exponent (alpha) obtained by fitting the data in the region of q = 0.1-0.6 nm(-1) to the power law (I = I(0)q(-alpha)) is a linear function of illite particle thickness. Therefore, illite particle thickness could be predicted by the linear relationship as long as the thickness is within the limit where alpha <4.0.
Keywords: Illite